(untitled) (Chemical Engineering Research Bulletin, 2026)
Black tea waste (BTW) has been studied as a low-cost adsorbent for the removal of a binary mixture of dyes (Crystal Violet (CV) & Safranin (SF)) from an aqueous solution by batch adsorption mode. The study has been performed at 25℃. Adsorption isotherm has been determined separately for CV and SF. Langmuir isotherm fits very well with experimental data for both SF and CR with R2 value, 0.999. The Langmuir parameters are determined for individual dyes. The maximum adsorption capacities of BTW for CV and SF in a single solution system are found to be 147.06 mg/g and 128.20 mg/g respectively. Equilibrium adsorption for the binary mixture of dyes is analyzed by extended Langmuir model, and this model is found to describe the adsorption behavior of the binary mixture satisfactorily. The adsorbent is characterized by Brunauer-Emmett-Teller (BET) analysis which gives an external surface area of 3.0744 m2/g. Chemical Engineering Research Bulletin: 24 (Issue 1): 95-104